2000
DOI: 10.1271/bbb.64.1041
|View full text |Cite
|
Sign up to set email alerts
|

α-Amylase Inhibitors from Roselle (Hibiscus sabdariffaLinn.) Tea

Abstract: A roselle (Hibiscus sabdariffa Linn.) tea extract was found to have high inhibitory activity against porcine pancreatic alpha-amylase. Hibiscus acid and its 6-methyl ester were respectively isolated as active principles from the 50% methanol and acetone extracts of roselle tea. The activity of each isolate was compared to that of structurally related citric acid, a previously known inhibitor of fungal alpha-amylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(137 citation statements)
references
References 19 publications
2
133
0
2
Order By: Relevance
“…Hence, to investigate the effects of the ester moiety together with the caffeoyl moiety against -glucosidase inhibition, we synthesized or purchased a series of caffeoyl ester 2-8 and methyl caffeate analogs 9-14, and tested for sucrase and maltase inhibitory activities. The compounds tested included four linear alkyl caffeates (2-4), two branched-chain alkyl caffeates (5, 6), phenyl caffeate (7), a ketone analog (10), methyl dihydrocaffeate (11), and two trihydroxycinnamates (13,14), and chlorogenic acid (8), caffeic acid (9), and methyl protocatechuate (12) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, to investigate the effects of the ester moiety together with the caffeoyl moiety against -glucosidase inhibition, we synthesized or purchased a series of caffeoyl ester 2-8 and methyl caffeate analogs 9-14, and tested for sucrase and maltase inhibitory activities. The compounds tested included four linear alkyl caffeates (2-4), two branched-chain alkyl caffeates (5, 6), phenyl caffeate (7), a ketone analog (10), methyl dihydrocaffeate (11), and two trihydroxycinnamates (13,14), and chlorogenic acid (8), caffeic acid (9), and methyl protocatechuate (12) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…2) In recent years, many efforts have been made to search for effective -glucosidase inhibitors from natural sources in order to develop a physiological functional food or to discover lead compounds for medicinal usage against diabetes. 3) In the course of our search for rat intestinal -glucosidaseinhibiting principles from various plants, we have isolated and identified several active compounds from plants grown in Asian regions, including Japan, [4][5][6][7] Thailand, 8,9) China, 10,11) and Nepal. 12) In this paper, we present the results of a screening of plants cultivated in Tanegashima, a southern island of Japan, for rat intestinal -glucosidase inhibition.…”
mentioning
confidence: 99%
“…Intestinal α-glycosidase and pancreatic α-amylase help in digestion of complex carbohydrates present in the food into bioavailable monosaccharide and plays an important role in postprandial hyperglycaemia; therefore inhibition of these enzymes has been reported as an effective mechanism for the control of postprandial hyperglycaemia. Hibiscus acid (hibiscus-type (2S,3R)-hydroxycitric acid lactone) have been shown as a potent inhibitor of pancreatic α-amylase and intestinal α-glucosidase and pancreatic α-amylase activity [28,29]. In another study, Adisakwattana et al [30], conducted an in vitro study and reported Roselle extracts as an effective inhibitor of pancreatic α-amylase.…”
Section: Hypo-lipidemic Effectsmentioning
confidence: 99%
“…During the last 40 years, a large number of glucosidase inhibitors have been isolated from plants and micro-organisms 1 and some of these were developed as drugs to control type II or noninsulin dependent diabetes 2 . Different inhibitors isolated from plants and microorganisms include diverse types of compounds like acarbose, isoacarbose, cyclodextrins, acarviosine-glucose and hibiscus acid [3][4][5][6] . Although the list of α-glucosidase inhibitors isolated from various biological sources are long, yet the bioactive molecules of traditional antidiabetic herbal drugs characterized are few in number.…”
Section: Introductionmentioning
confidence: 99%